2000
DOI: 10.1097/00000542-200007000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiologist Direction and Patient Outcomes

Abstract: The relationship between physicians and nurses in the delivery of anesthesia care is politically and financially charged, and hotly debated. Against this backdrop, federal regulators have proposed dropping a Medicare requirement that nurse anesthetists be supervised by a physician. Proponents note that the new regulations would resolve inconsistencies between Medicare supervisory requirements and state law, while opponents voice concerns for patient safety. This Issue Brief describes the current controversy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 19 publications
2
97
0
4
Order By: Relevance
“…43 However, there are limited outcome data regarding provider models in specific areas, such as perioperative care. Silber et al 14,15 reported that the mortality rate and failure to rescue were lower when anesthesiologists directed anesthesia care and the anesthesiologist was board certified. Aiken et al 16,17 found that a lower nurse-to-patient ratio and higher level of education of the nurses decreased postoperative mortality and failure to rescue.…”
Section: Discussionmentioning
confidence: 99%
“…43 However, there are limited outcome data regarding provider models in specific areas, such as perioperative care. Silber et al 14,15 reported that the mortality rate and failure to rescue were lower when anesthesiologists directed anesthesia care and the anesthesiologist was board certified. Aiken et al 16,17 found that a lower nurse-to-patient ratio and higher level of education of the nurses decreased postoperative mortality and failure to rescue.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason for the differences observed between these cohorts is variation in nurse staffing levels, which have been shown to be a robust independent predictor of postoperative death in 217 440 surgical patients 28 . In another study involving 232 343 surgical patients at 168 hospitals in the state of Pennsylvania, USA, higher patient to nursing staff ratios were associated with a higher risk-adjusted postoperative mortality rate 29 .…”
Section: Discussionmentioning
confidence: 99%
“…These ratios relate to ward patients only and do not reflect the contribution of high-dependency unit or ICU beds. Based on the results from previous studies 28,29 , it is possible that the lower patient to nurse ratios in the US cohort contributed to the lower risk-adjusted mortality rate observed.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we sought to investigate the relationship between nurse staffing levels and in-hospital mortality in a pilot study using a large administrative database from the state of Michigan [27] in combination with a widely known, inexpensive, and publicly available measure of nurse staffing levels collected by the American Hospital Association (AHA) [7]. Prior work has established the AHA's measure as an approximation of hospitals' nurse staffing practices in the inpatient setting [16,22,25,26,36,39,41].…”
Section: Introductionmentioning
confidence: 99%